ROLE OF COASTAL SEDIMENT ON SOIL NUTRIENT AVAILABILITY AND OIL PALM YIELD AT PEATLANDS - Denah Suswati; Tino Orciny Candra; Yarlina Yacoub (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2016)
Peatlands which is limited in chemical, physical and ecology require appropriate management for oil palm plantation. Coastal sediment as an ameliorant in peatlands increased productivity some crops. This study aims determining the effect of the doses of coastal sediment as ameliorant on peatlands to the availability of N, P, K, Ca, Mg and Na oil palm plantations. This research was performed in the area of oil palm plantation in Kubu Raya district, Borneo, Indonesia. Experimental design employed randomized block design with 4 levels of coastal sediment doses (L), i.e. L0 = 0 t ha-1; L1 = 20 t ha-1; L2 = 40 t ha-1; L3 = 60 t ha-1 with three replication. The results showed that the application of coastal sediment at 40 t ha-1 in oil palm plantations significantly increased soil pH, availability of N, K, Ca and Mg, while P was not significantly different